Breaking rules children in conflict with the law and the juvenile justice process. (Quezon City Save the Children-UK, 2004)
Complete findings of three studies that looked into the profile of children in conflict with the law, and their situation and experiences in the justice administration process. The studies were conducted in the three main urban centers in the Philippines, namely, Metro Manila, Cebu City and Davao City. These studies also present specific cases, highlight emerging gaps and issues, and put forward recommendations for the five pillars of justice - the community, law enforcement, prosecution, the courts and correction - to address the needs and concerns, and promote the rights of children who come into conflict with the law. Includes summary and consolidation of the three researches.
Children in conflict with the law n the experience in the Philippines : a summary / John Parry Williams -- Research on the situation of children in conflict with the law in selected Metro Manila Cities / Adhikain para sa Karapatang Pambata n Ateneo Human Rights Center -- Children in conflict with the law in Cebu : profile and experience with the juvenile justice process / Felisa U. Eternadi with Ching Li Ye and Cresencio Bermudez, Jr. -- Understanding children in conflict with the law : contradictions on victimisation, survivor behaviour and the Philippine justice system : a study of the situation of children in conflict with the law in Davao / Mae Fe Templa.
PDF format
CD-ROM
Keywords: Juvenile justice, Administration of -- Philippines; Juvenile delinquency -- Philippines -- Case studies; Children's rights -- Philippines